Presence of inhibitors and effect of the glumes in the imbibition of seeds of sweet sorghum - dos Santos, Dora Suely Barbosa; Tillmann, Maria Angela André; Peters, José Antônio (Pesquisa Agropecuaria Brasileira, 1991)
Sweet sorghum seeds (Sorghum bicolor (L.) Moench), cv BR-501, at two maturity stages with and without glumes were used in this study. The objectives were: 1) to identify if the glumes have influence on the water absortion by the seed; 2) to detect and characterize the inhibitors present in the glumes, since the removal of the glumes causes an increase in the physiological quality of the seed. Seeds with glumes present a higher imbibition velocity, maybe due to higher water retention in the glumes. However, mature seeds with glumes showed higher percentage of absorbed water. So, it was concluded that the glumes do not have influence on water absortion by the seeds, considering the occurrence of imbibition stabilization around 13 hours for mature seeds with and without glumes, and 11 hours for immature seeds. In relation to the presence of inhibitors the conclusion is that the immature sorghum seed glumes have fenolic inhibitors which are not detected in the glumes of mature seeds.